ANALISIS PENGARUH STRUKTUR PERTUMBUHAN PENJUALAN, STRUKTUR MODAL INFLASI, INDEKS HARGA SAHAM GABUNGAN, NILAI TUKAR MATA UANG ASING TERHADAP NILAI PERUSAHAAN YANG TERCATAT DIINDEKS LQ45: (Studi kasus pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia Tahun 2015 – 2019) - Fitrah Aulina Fitrah Aulina; Silfrida Yulianti Silfrida Yulianti; Hasanuddin Hasanuddin; Herry Wira Wibawa Herry Wira Wibawa (LPPM Swadaya Institute of Business and Communication, 2023)
The development of the business world at this time is getting higher. It can be seen from the many companies that are competing to attract investors to cooperate, with the aim that investors are interested in investing in the company. Before investors make a choice, it is necessary for these investors to look at financial reports, especially company value and financial reports. This study aims to analyze (1) the effect of sales growth, capital structure, inflation, composite stock price index, and foreign currency exchange rates on firm value simultaneously. (2) the effect of sales growth on firm value, (3) the effect of capital structure on firm value, (4) the effect of inflation on firm value, (5) the effect of the composite stock price index, (5) the effect of foreign currency values on firm value. The sampling method used is the purposive sampling method. The data used in this study were obtained from financial reports published through www.idx.co.id during the period January 2015 - December 2019. The population in this study were companies listed on the LQ 45 index and listed on the Indonesia Stock Exchange, totaling 45 companies with the number of samples 10 companies. Analysis of the data used is by using multiple regression analysis. Furthermore, the hypothesis testing used is the partial test (t test) and linear simultaneous test (f test). The hypothesis results show that (1) sales, and capital structure, have a significant effect on firm value simultaneously, (2) inflation, the composite stock price index, and foreign exchange rates have no significant effect on firm value simultaneously.